2016
DOI: 10.1136/jclinpath-2016-204103
|View full text |Cite
|
Sign up to set email alerts
|

Primary cilia are increased in number and demonstrate structural abnormalities in human cancer

Abstract: The results show upregulation of primary cilia and the presence of structural defects in a wide range of human cancer tissue samples demonstrating association of dysregulation of primary cilia with human cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 18 publications
0
26
1
Order By: Relevance
“…The proposed role for ARL13b to act as a tumor suppressor raises the possibility that ARL13b expression in PC could be altered during tumor progression, and in fact, most authors now use two different markers for PC to validate their findings. One study used an antibody for ciliary rootlet coiled-coil (CROCC) for the identification of PC displaying an increase in PC numbers in lung, colon, and pancreatic adenocarcinoma compared to the respective normal tissue and unaltered expression in stomach, prostate, and breast cancer [120]. The findings obtained using CROCC for the identification of PC are somewhat different from the PC expression patterns in the respective tumor tissues described above.…”
Section: General Considerations and Remarksmentioning
confidence: 99%
“…The proposed role for ARL13b to act as a tumor suppressor raises the possibility that ARL13b expression in PC could be altered during tumor progression, and in fact, most authors now use two different markers for PC to validate their findings. One study used an antibody for ciliary rootlet coiled-coil (CROCC) for the identification of PC displaying an increase in PC numbers in lung, colon, and pancreatic adenocarcinoma compared to the respective normal tissue and unaltered expression in stomach, prostate, and breast cancer [120]. The findings obtained using CROCC for the identification of PC are somewhat different from the PC expression patterns in the respective tumor tissues described above.…”
Section: General Considerations and Remarksmentioning
confidence: 99%
“…[2,[147][148][149] Medulloblastoma comprises four major subgroups: sonic hedgehog (SHH), WNT, group 3, and group 4. [2,[147][148][149] Medulloblastoma comprises four major subgroups: sonic hedgehog (SHH), WNT, group 3, and group 4.…”
Section: Hedgehog Signaling Regulates Cancer Cell Proliferation Throumentioning
confidence: 99%
“…In contrast with the above examples, cilia have been shown to persist in a range of tumors (Fu et al, 2014;Yasar et al, 2017) and can be found in medulloblastomas exhibiting activation of Hh or Wnt signaling (Han et al, 2009). Strikingly, tumorigenesis is blocked in a medulloblastoma mouse model driven by constitutively active SMO when primary cilia are genetically ablated (Han et al, 2009).…”
Section: Cilia As Tumor Promotersmentioning
confidence: 98%